Biochemical mechanisms of tributyltin chloride-induced cell toxicity in Sertoli cells - Chen, Pengchen; Chen, Junhui; Zhang, Wei; Tang, Li; Cheng, Guangqing; Li, Huiying; Fan, Tianyun; Wang, Jigang; Zhong, Wenbin; Song, Yali (Ecotoxicology and environmental safety, 2023)
Tributyltin chloride (TBTCL) is a widely used fungicide and heat stabilizer in compositions of PVC. TBTCL has been detected in human bodies and potentially causes harmful effects on humans’ thyroid, cardiovascular and other organs. As one of the first examples of endocrine disruptors, the toxicity effects of TBTCL on the male reproduction system have aroused concerns. However, the potential cellular mechanisms are not fully explored. In the current study, by using Sertoli cells, a critical regulator of spermatogenesis as a cell model, we showed that with 200 nM exposure for 24 h, TBTCL causes apoptosis and cell cycle arrest. RNA sequencing analyses suggested that TBTCL probably activates endoplasmic reticulum (ER) stress, and disrupts autophagy. Biochemical analysis showed that TBTCL indeed induces ER stress and the dysregulation of autophagy. Interestingly, activation of ER stress and inhibition of autophagy is responsible for TBTCL-induced apoptosis and cell cycle arrest. Our results thus uncovered a novel insight into the cellular mechanisms for TBTCL-induced toxicology in Sertoli cells. [Display omitted] •Tributyltin chloride causes apoptosis and cell cycle arrest in mouse Sertoli cells.•Tributyltin chloride induces endoplasmic reticulum (ER) stress and autophagy flux blockade.•Tributyltin chloride induced apoptosis and cell cycle arrest via autophagy process.•Disordered autophagy process is responsible for tributyltin chloride-induced apoptosis and cell cycle arrest.•We provided a new understanding in the mechanisms of TBTCL-induced testis toxicity.